2013
DOI: 10.1017/jns.2013.17
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of inflammation by selenium and selenoproteins: impact on eicosanoid biosynthesis

Abstract: Uncontrolled inflammation is a contributing factor to many leading causes of human morbidity and mortality including atherosclerosis, cancer and diabetes. Se is an essential nutrient in the mammalian diet that has some anti-inflammatory properties and, at sufficient amounts in the diet, has been shown to be protective in various inflammatory-based disease models. More recently, Se has been shown to alter the expression of eicosanoids that orchestrate the initiation, magnitude and resolution of inflammation. Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(57 citation statements)
references
References 104 publications
(131 reference statements)
1
50
0
4
Order By: Relevance
“…4C). In line with the reported anti-inflammatory role of selenium (Mattmiller, Carlson, & Sordillo, 2013;Mocchegiani et al, 2014), we found that selenate supplementation resulted in the suppression of HF diet-induced inflammation in WAT (Fig. 4B).…”
Section: Discussionsupporting
confidence: 90%
“…4C). In line with the reported anti-inflammatory role of selenium (Mattmiller, Carlson, & Sordillo, 2013;Mocchegiani et al, 2014), we found that selenate supplementation resulted in the suppression of HF diet-induced inflammation in WAT (Fig. 4B).…”
Section: Discussionsupporting
confidence: 90%
“…SeP acts as an intracellular antioxidant in phagocytes, modulating inflammatory response via switching macrophage differentiation from M1 to M2 and, of consequence, limiting pathogenicity and oxidative damage [176,177]. On the other hand, SeP serum levels were shown to be lowered by acute-phase inflammatory response [178,179].…”
Section: Liver-released Compoundsmentioning
confidence: 99%
“…Among human selenoproteins, glutathione peroxidase (GPX), thioredoxin reductase (TXNRD), and iodothyronine deiodinase (DIO) represent the best‐characterized selenoenzymes of the antioxidant defense and endocrine systems . Certain selenoproteins have been proven to be essential; that is, GPX4, TXNRD1, TXNRD2, and others are of high pathophysiological relevance because of their anti‐inflammatory and antioxidative properties, which render Se as a central biological micronutrient during the acute phase of ischemia/reperfusion (I/R) and inflammation in cardiovascular patients . Selenoproteins are not only the responsible players to translate an increased Se supply into protective biological action, but circulating selenoproteins can also be used as markers to determine the Se status in the patients before or during supplementation .…”
Section: Introductionmentioning
confidence: 99%